Dracula in Film: Coppola and Shore. Comparative Analysis of a Literary Archetype - Agusti Aparisi, Carme (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2017)
The vampire myth is one of the most attractive of all time. Since the creation of archetypes in literature, a multitude of tales have attempted to characterise this character’s idiosyncrasies. But it is undoubtedly film that has recreated and constructed the different nuances of this archetype. Dracula has become popular and come to form part of the community of the myth thanks to the different versions given by the seventh art. Coppola succeeded in giving it a humanising vision and since then there have been many constructions and deconstructions of the character. We propose taking a brief tour, starting with the characteristics of the monster created by Stoker, then taking in Coppola and his new vision and eventually arriving at Hollywood’s latest reinterpretation of the myth: “Dracula, the legend never told,” and analysing the characteristics of the character’s new reinvention.